Looking at the Molecular Target of NS5A Inhibitors throughout a Population Highly Affected with Hepatitis C Virus - Ramos, Diogo (2023)
Hepatitis C virus (HCV) is associated with liver damage and an increased progression rate to cirrhosis and hepatocellular carcinoma. In Portugal, it is prevalent in vulnerable populations such as injection drug users (IDU). HCV is characterized by a high intra-host variability, and the selecting driving forces could select variants containing resistance-associated substitutions (RAS) that reduce treatment effectiveness. The main goal of this study was to analyze the sequence variation of NS5A in treatment-naïve IDU. The epidemiological and clinical status of hepatitis C were analyzed, and samples were sequenced by Sanger and Next-Generation sequencing (NGS) to assess RAS and confirm HCV subtypes. Phylogenetic classification was concordant: 1a, 52.4%; 1b, 10.7%; 3a, 20.2%; 4a, 8.3%; 4d, 7.1%; and one 2k/1b recombinant. A 1a/3a mixed infection was detected by NGS. RAS were found in 34.5% (29/84) of samples using Sanger sequencing, while in 42.9% (36/84) using NGS. In sequences from subtypes 1a and 1b, RAS K24R, M28V, Q30H/R, H58D/P/Q/R, and RAS L31M and P58S were detected, respectively. In subtype 3a, RAS A30S/T, Y93H and polymorphisms in position 62 were identified. Additionally, RAS P58L was detected in genotype 4. The strategy used for the molecular survey of baseline HCV resistance is of particular importance to achieve treatment effectiveness and contribute to the elimination of hepatitis C.